The Effect of Price and Product Quality on Purchasing Decisions for Scarlett Whitening Cosmetic Products in Samarinda - Manurung, Indah Sari R; Wediawati, Tuti (Jurnal Ekonomi, 2024)
This research aims to determine the influence of price and product quality on purchasing decisions for Scarlett cosmetic products in Samarinda, both partially and simultaneously and to find out which variables have the most influence on decision making. The research method used is the descriptive method. The sample is 100 respondents. This type of research is quantitative research. The analytical tools used are Ui validity, Ui reliability, classical assumption test, multiple linear regression, coefficient of determination, t test (partial) and f test (simultaneous). Based on the research results, several conclusions were obtained, namely that price and product quality on purchasing decisions for Scarlett whitening cosmetic products have a correlation of 0.571, which means the relationship is strong. Partially, price has a significant influence on purchasing decisions for Scarlett Whitening products and product quality has a significant influence on purchasing decisions for Scarlett Whitening products. And simultaneously the price and quality of the product have a significant influence on purchasing decisions for Scarlett Whitening products.